Environmental chemometrics - Hanrahan, Grady (CRC, 2009)
Chapter 1. Introduction -- Chapter 2. Review of Statistics and Analytical Figures of Merit -- Chapter 3. Quality Assurance in Environmental Analysis -- Chapter 4. Experimental Design and Optimization Techniques -- Chapter 5. Time Series Analysis -- Chapter 6. Multivariate Data Analysis